2009
DOI: 10.1007/s00421-009-1207-2
|View full text |Cite
|
Sign up to set email alerts
|

Do sessions of cryostimulation have influence on white blood cell count, level of IL6 and total oxidative and antioxidative status in healthy men?

Abstract: The influence of extremely low temperatures on the human body and physiological reactions are not fully recognized. It has been postulated that cryostimulation could modify immunological reactions, leukocytes mobilization and levels of cytokines. The aim of this research was to estimate the influence of a ten sessions 3-min-long exposures to cryogenic temperature (-130 degrees C) on the white blood cell (WBC) count, level of IL6 and the total oxidative and antioxidative status in 15 young, clinically healthy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 31 publications
7
64
3
Order By: Relevance
“…Each cryostimulation session lasted 3 min. The duration of each session and the temperature of the cold chamber were similar to our previous studies [6,7,11,21], and similar to the prevalent practice. Glasses, contact lenses and all jewelry were removed before the participants entered the chamber.…”
Section: Statisticssupporting
confidence: 71%
See 1 more Smart Citation
“…Each cryostimulation session lasted 3 min. The duration of each session and the temperature of the cold chamber were similar to our previous studies [6,7,11,21], and similar to the prevalent practice. Glasses, contact lenses and all jewelry were removed before the participants entered the chamber.…”
Section: Statisticssupporting
confidence: 71%
“…Literature describes a number of changes occurring in the body after exposure to cold. Usually, the changes concern the endocrine system [3,4,], the immunological system [3][4][5][6] lipid profile [7], and hematological values [8][9][10]. The impact of cryostimulation on the level of physical fitness remains considerably unexplored, both in relation to the components of aerobic and anaerobic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The response of the body to cold temperatures occurs through changes in the endocrine system (increase in adrenocorticotropin concentration, β-endorphins, epinephrine, norepinephrine and testosterone concentration in men) [1][2][3][4], circulatory system (contraction of blood vessels in the skin, then their dilation and congestion of the skin) [5], neuromuscular system (reduction of muscle tension, decrease in nerve conduction velocity) [6] and immunological system (increase in cell-mediated and humoral immunity) [1,[7][8][9][10]. Moreover, whole body cooling influences the prooxidant-antioxidant balance in blood [11][12][13][14], and has an anti-inflammatory [15] as well as an analgesic effect [6]. This analgesic effect is caused by the combination of increased β-endorphin concentration and decreased nerve conduction in afferent fibers, which are responsible for pain reception [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that cryostimulation mobilizes the white blood cells, particularly immunocompetent lymphocytes [4,15,21,22]. The effect on red blood cells has not been positively confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Banfi et al reported that whole-body cryotherapy is not deleterious to cardiac function in healthy individuals [1]. Documented analgesic, anti-inflammatory and antioedematous action reduces increased muscle tension and therefore cryotherapy has been increasingly often applied in sport and medicine, in combination with additional forms of treatment [13,14,25,34,36].It is postulated that cryostimulation mobilizes the white blood cells, particularly immunocompetent lymphocytes [4,15,21,22]. The effect on red blood cells has not been positively confirmed.…”
mentioning
confidence: 99%